Development of a vortex generating flume for the removal of phosphorus from waste streams - McDonald, Russ R (Kansas State University, 2007)
Feedlots, animal production facilities, and agricultural lands are point and non-point sources for nutrient enrichment of surrounding waterways and result in human enhanced eutrophication. Artificial elevation and increased enrichment from animal wastes, fertilizer, and runoff greatly increase the speed of this natural process and leads to degraded water quality, algae blooms, and fish kills. Phosphorous is typically the limiting nutrient for plant growth, and thus is the main focus of this paper. Phosphates enable excessive and choking plant growth that lead to depleted dissolved oxygen and excessive decaying plant matter, subsequently damaging the aquatic ecosystem. In order to provide an inexpensive and feasible solution to minimize phosphate eutrophication, a passive, vortex generating flume has been proposed to provide the necessary mixing for the removal of phosphorus from waste waters. Preliminary tests with dye tracers and electrolyte pulse injections have been conducted to model the flow characteristics and determine the residence time under a variety of flow conditions, angle of inclination and flow rate. The flume was modeled by two methods: four continuously stirred tank reactors (CSTRs) in series and as four CSTRs in series operating in parallel with a plug flow reactor (PFR). The hydraulic model fit a total of five parameters to the experimental data: Residence time, the inlet concentrations of the electrolyte pulse tracer, and the injection times of the tracer to both types of reactors. The kinetic model was built based on data collected from a different study of swine lagoons using magnesium chloride to precipitate phosphorus as the mineral struvite. The precipitation kinetics were modeled using first order and irreversible reaction and incorporated into the hydraulic model. The vortex generating flume provided an operating space that sufficiently removed phosphorus from the waste stream. Future work will include pilot scale testing of the model using waste streams and the investigation of a scour to minimize solid formation in the flume.
Keywords: Eutrophication; Phosphorus; Phophate; Chemical Precipitation; Agricultural Waste; Engineering, Chemical (0542); Engineering, Environmental (0775); Environmental Sciences (0768)